The optimised design of HVAC systems - Jonathan Wright (1986)
The workable design of HVAC (Heating Ventilating and Air Conditioning) systems is based upon sizing the components individually to meet a peak duty of a nominal operating point. Growing economic pressure demands more cost effective and efficient designs, but the appraisal of alternative solutions is limited by short design and construction times. The design of HVAC systems can benefit from the application of numerical optimisation methods as these allow the rapid appraisal of alternative schemes and the sizing of the components simultaneously for criteria such as minimum first cost, operating cost, life—cycle cost or primary energy consumption. Optimisation problems can be categorised according to the characteristics of the functions used to appraise the solutions and those of the constraints on the problem. This thesis discusses the formulation of EVAC system design problems in this context and describes the development of an optimisation procedure which is based upon a data base of manufactured components and operating parameters such as controller setpoints, mass flow rates and temperatures. The thesis describes several objective functions used in the appraisal of solutions and describes the use of constraint functions in restricting the solution to a practicable design. UVAC system optimised design problems can be solved using direct search methods. The implementation of three direct search algorithms is described and the limitations of each discussed. Conclusions are drawn and the characteristics of HVAC system optimised design problems used to make recommendations for the future development of an idealized algorithm. The thesis describes the development and structure of the optimised design program and its integration with an existing suite of simulation programs. The application of the program to the design of example heat recovery systems is given and the potential use of the software in other applications described together with proposals for the development of the procedure as a design tool.